Trajectories of Loneliness and Psychosocial Functioning - Hutten, Elody; Jongen, Ellen M. M.; Verboon, Peter; Bos, Arjan E. R.; Smeekens, Sanny; Cillessen, Antonius H. N. (Frontiers in Psychology, 2021)
The present study examined the relationship between developmental patterns of loneliness and psychosocial functioning among adolescents (9–21 years; N = 110, 52% male). Four-wave longitudinal data were obtained from the Nijmegen Longitudinal Study (NLS) on Infant and Child Development. Loneliness was measured at 9, 13, 16, and 21 years of age and anxiety, depression and self-esteem at 9 and 21 years of age. Using k-means cluster analysis, three trajectories of loneliness were identified as “stable low” (56% of the subjects), “high decreasing” (22% of the subjects), and “low increasing” (22% of the subjects). Importantly, trajectories of loneliness across adolescence significantly predicted psychosocial functioning in young adulthood. Both the “high-decreasing” and “low-increasing” loneliness clusters were associated with higher risk of depression and lower self-esteem compared to the “stable low” loneliness cluster. The “low-increasing” loneliness cluster was associated with higher risk of anxiety compared to the “stable low” loneliness cluster. These results indicate that loneliness in adolescence is a vulnerability that manifests itself in higher levels of anxiety and depression and lower self-esteem in young adulthood.